Long-term survival after targeted therapy plus immunotherapy without chemotherapy in advanced gallbladder carcinoma: a case report and literature review - Chen, Zhitao; Wu, Yuhao; Ding, Chenchen; Gu, Yangjun; Wu, Weilin; Li, Qiyong (Frontiers in Immunology, 2025)
BackgroundGallbladder carcinoma (GBC) is a highly aggressive malignancy with limited treatment options and poor prognosis, particularly in advanced stages. Traditional chemotherapy often yields modest outcomes and can be poorly tolerated.Materials and methodsWe report a case of a 59-year-old woman with stage IVA GBC who was unable to tolerate first-line gemcitabine and cisplatin due to severe adverse effects. Next-generation sequencing revealed a moderate tumor mutation burden and microsatellite-stable status. Based on a multidisciplinary team assessment, she received camrelizumab (PD-1 inhibitor) plus apatinib (VEGFR2 inhibitor).ResultsAfter 11 cycles, imaging demonstrated significant tumor regression and reduced invasion, enabling successful radical resection. Postoperative pathology confirmed moderately differentiated adenocarcinoma with no lymph node involvement. The patient remained disease-free for over two years. Following isolated cervical lymph node metastasis, combination therapy with camrelizumab and surufatinib resulted in complete remission. She continues on maintenance immunotherapy without recurrence five years post-diagnosis.ConclusionThis case highlights the promising potential of targeted therapy and immunotherapy in converting unresectable GBC to operable disease and achieving durable remission, even in patients lacking classic immunotherapy biomarkers. Personalized, non-chemotherapy-based strategies may offer viable alternatives for selected patients.